Fixed Sample Size as an Internal Control - Dianita Meirini; Atik Tri Andari; Elmi Rakhma Aalin (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
This study aims to analyze the effectiveness of internal control on two existing Community Banks in Tulungagung. According to Bank Indonesia rank, Tulungagung occupies the 1st position of the highest NPL in 2016. The effectiveness analysis of internal control is performed on the second Community Bank crediting system that includes qualitative and quantitative aspects analysis. Qualitative aspect analysis is based on Audit Standard applicable in Indonesia (AS) Section 319 Consideration of Internal Control in Audit of Financial Statements paragraph 07. Quantitative aspect analysis using Fixed Sample Size with a 95% confidence level and fault tolerance / DUPL (Desired Upper Precision Limit) = 5%. The result of the qualitative aspect shows the internal control system in both Community Banks is effective. It’s based on conformity between AS Section 319 and its implementation on both Community Bank. Total 20 questions for conformity analysis, 1st Community Bank for the next called BPR A is 80% appropriate, 2nd Community Bank for the next called BPR B is 60% appropriate. The rest questions are used as an attribute on quantitative analysis. The result of the quantitative aspect shows the internal control system in both Community Banks is not effective. This is because the AUPL (Achieved Upper Precision Limit) from three attribute samples analyzed exceed specified DUPL, that is: a) Authorization of credit approval documents AUPL = 18%, b) Completeness of supporting documents attached AUPL = 28%, and c) Verification of transaction correctness and correctness of ceiling calculation AUPL credit = 29%.